ALVEOLAR SOFT PART SARCOMA - Sanggam B. Hutagalung; Jekson Martiar Siahaan (Majalah Ilmiah METHODA, 2018)
Alveolar Soft Part Sarcoma (ASPS) is a rare sarcoma, this sarcoma accours around 0,2 – 0,9% of all soft tissue sarcomas. This tumour can occur at any age, but the peak incidence is in the age range of 15 – 35 years, rarely under the age of 5 years and after the age of 50 years. In adults, ASPS most often occur in deep soft tissues in the lower extremites, especially the anterior part of the thighs and buttocks. But in children and infants these tumours often occur in the area of the head and neck, especially the tongue and eyes. Tumours that occur in the head and neck are usually smaller in size may be due to earlier detection. Diagnostic of ASPS can be through CT – Scan/MRI examination, Fnab Citology, Histopathology, and Immunophenotype.